2012
DOI: 10.1007/s11095-012-0707-7
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Quantification of CYP Enzymes to Establish In Vitro/In Vivo Scaling Factors for Intestinal and Hepatic Metabolism in Beagle Dog

Abstract: CYP expression in dog liver and intestine was characterized, providing a basis for in vitro/in vivo scaling of intestinal and hepatic metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Figure 1 shows the distribution of the different CYPs in liver and small intestinal mucosa of human 9, 10 and dog 11 . The liver has the highest content of drug metabolizing CYPs and is the most important organ for CYP mediated drug elimination.…”
Section: Dog-human Cyp Similarities and Differencesmentioning
confidence: 99%
“…Figure 1 shows the distribution of the different CYPs in liver and small intestinal mucosa of human 9, 10 and dog 11 . The liver has the highest content of drug metabolizing CYPs and is the most important organ for CYP mediated drug elimination.…”
Section: Dog-human Cyp Similarities and Differencesmentioning
confidence: 99%
“…There is a great interest in quantifying endogenous human drug metabolizing enzymes and drug transporters to assist better understanding of the absorption, distribution, metabolism, and excretion (ADME) of drugs. LC-MS/MS-based quantitation of the cytochrome P450 enzyme family (Seibert et al, 2009;Sakamoto et al, 2011;Williamson et al, 2011;Heikkinen et al, 2012), transporters (Li et al, 2008;Sakamoto et al, 2011), and UDP-glucuronosyltransferases (Sakamoto et al, 2011) have been reported in the literature to assist the development of predictive clearance models. In this report, we described a fast, sensitive, and robust LC-MS/MS method to quantify absolute AOX1 levels and the method was applied to AOX1 quantification of human liver cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…Linear correlations demonstrated between metabolism or transport of specific probes and corresponding protein abundance in vitro confirm that protein concentration is a determinant of activity. However, it is well recognized that enzyme and transporter activity is also affected by other factors such as accessory proteins, energy sources, co‐factors, and the specific membrane and aqueous environments of the protein .…”
Section: Examples Of the Utility Of Protein Abundance Data For Ivive mentioning
confidence: 64%
“…Hepatic elimination is a significant determinant of PK and it is not surprising that the majority of LC‐MS/MS‐based proteomic studies characterizing enzyme and transporter abundances have done so in the human liver [, . Furthermore, other human tissues important for PK, namely intestine , kidneys , and lungs , and the blood–brain barrier have received attention as well as various tissues in animal species . A significant part of the existing data on CYP abundance is based on immunochemical protein quantification methods and consequently applications for IVIVE and PBPK have employed these data.…”
Section: Examples Of the Utility Of Protein Abundance Data For Ivive mentioning
confidence: 99%
See 1 more Smart Citation